Hermeneutika Pembebasan Farid Esack Dari Perspektif Revolusi Ilmiah Thomas Kuhn - Permana, Ridani Faulika; Zubaidi, Sujiat; Nuriz, M. Adib Fuadi; Khakim, Usmanul; Mumtazi, Fahman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Farid Esack on Hermeneutic of Liberation from Thomas Kuhnâ€™s Scientific Revolution Perspective This article aims to elaborate on Farid Esack’s Hermeneutic of Liberation from Thomas S Kuhn’s scientific revolution perspective. The background of this study is the liberation of society from apartheid hegemony in South Africa in the 1949-1991 period; Farid Esack - from the beginning engaged in the practical political movement and now focuses on the scientific field - gave rise to new methodical ideas in the study of the Koran i.e hermeneutics of liberation; which is an effort to fight against racist rulers. From Kuhn’s point of view, what Essack was doing was actually a scientific revolution. This assumption will be elaborated in this study. This study is a literature review using qualitative-content analysis as the data analysis technique. The results of this study are; first, his method of Qur’anic is a scientific revolution; which he supported the strengthening of the hermeneutical paradigm in the study of the Qur’an. In that way, secondly, as Kuhn requires that the new paradigm of scientific revolution must be supported by the scientific community, Farid Esack can be said to have a scientific community with Fazl Rahman, Hasan Hanafi, Mohamed Arkoun, Nasr Hamid Abu Zaid, etc. Thus, it is worth waiting for the success of this community revolution; to strengthen hermeneutics as a new paradigm in Qur’anic study in the future